Living plant-mediated synthesis of different shaped gold nanoparticles - Raju, D.; Paneliya, Nikita; Mehta, Urmil J. (Nanoscience and Nanotechnology Letters, 2014)
We demonstrate extracellular green synthesis of gold nanoparticles with different shapes and sizes by using live Prosopis juliflora L. seedling. The conversion of ionic to metallic gold nanoparticles by P. juliflora seedling was carried out in short period. The formed nanoparticles were characterized by UV, TEM, Diffraction and EDS. TEM shows well dispersed particles of different shapes and sizes. The percentage of different shapes of nanoparticles was calculated, most of the particles were spherical in shape (75%). The triangle nanoparticles were 10%, followed by squares (8%), hexagonal (5%) and rods (2%). The diffraction shows the formed nanoparticles are crystalline in nature and EDS confirms the formed nanoparticles are of gold. This shows P. juliflora seedling can synthesis different shapes of well dispersed nanoparticles.
Keywords: Gold; Nanoparticles; Prosopis juliflora; Shapes; synthesis; TEM